Barrier Pillar Design for Safe and Productive Longwall Mining - Stephen C. Tadolini (International Conference on Ground Control in Mining, 2013)
Effective barrier pillar design is an essential component for safe and productive underground coal mining. Barrier pillar design methodologies that incorporate sound engineering judgment have been used for practical everyday usage. The next logical step is to utilize numerical modeling techniques that help combine practical experience and empirical observations into barrier pillar design analysis. A case study is presented that describes the barrier pillar design process, but also highlights the importance of considering the global mine response by evaluating: adjacent pillar stabilities, impact of intersection and entry widths, capacity of primary and secondary bolting systems and rib stabilization used for the safe and efficient removal of the longwall face equipment.